Hypoxia-induced cytotoxic drug resistance in osteosarcoma is independent of HIF-1Alpha. - Jennifer Adamski (Public Library of Science (PLoS), 2013)
Survival rates from childhood cancer have improved dramatically in the last 40 years, such that over 80% of children are now cured. However in certain subgroups, including metastatic osteosarcoma, survival has remained stubbornly poor, despite dose intensive multi-agent chemotherapy regimens, and new therapeutic approaches are needed. Hypoxia is common in adult solid tumours and is associated with treatment resistance and poorer outcome. Hypoxia induces chemotherapy resistance in paediatric tumours including neuroblastoma, rhabdomyosarcoma and Ewing's sarcoma, in vitro, and this drug resistance is dependent on the oxygen-regulated transcription factor hypoxia inducible factor-1 (HIF-1). In this study the effects of hypoxia on the response of the osteosarcoma cell lines 791T, HOS and U2OS to the clinically relevant cytotoxics cisplatin, doxorubicin and etoposide were evaluated. Significant hypoxia-induced resistance to all three agents was seen in all three cell lines and hypoxia significantly reduced drug-induced apoptosis. Hypoxia also attenuated drug-induced activation of p53 in the p53 wild-type U2OS osteosarcoma cells. Drug resistance was not induced by HIF-1α stabilisation in normoxia by cobalt chloride nor reversed by the suppression of HIF-1α in hypoxia by shRNAi, siRNA, dominant negative HIF or inhibition with the small molecule NSC-134754, strongly suggesting that hypoxia-induced drug resistance in osteosarcoma cells is independent of HIF-1α. Inhibition of the phosphoinositide 3-kinase (PI3K) pathway using the inhibitor PI-103 did not reverse hypoxia-induced drug resistance, suggesting the hypoxic activation of Akt in osteosarcoma cells does not play a significant role in hypoxia-induced drug resistance. Targeting hypoxia is an exciting prospect to improve current anti-cancer therapy and combat drug resistance. Significant hypoxia-induced drug resistance in osteosarcoma cells highlights the potential importance of hypoxia as a target to reverse drug resistance in paediatric osteosarcoma. The novel finding of HIF-1α independent drug resistance suggests however other hypoxia related targets may be more relevant in paediatric osteosarcoma.